Peran Sklerotium dan Bentuk Lain Patogen Rhizoctonia solani sebagai Sumber Inokulum Awal Penyakit Hawar Pelepah Padi - Suparyono Suparyono; Sudir Sudir (Jurnal Perlindungan Tanaman Indonesia, 1999)
Experiments were conducted in Sukamandi Experimental Station of the Research Institute for Rice (RIR), to evaluate the importance of sclerotia and other propagules as the primary inoculum of rice sheath blight. The trials were conducted during the growing season of 1996/1997. Two elite varieties, namely IR64 and Cisadane, were planted in plots of 2×2 m in size. Subplots were three different ways of crop establishment, i.e. transplanting with 20×20 cm distance, transplanting in-row with 10×40 cm, and direct seeding in row. Sub-sub plots were 6 different form of inoculum of R. solani, namely sclerotia, sclerotia+mycelium, fresh infected rice straw, decomposed infected rice straw, fresh infected weeds, and decomposed infected weeds. Checks were plots with no additional inoculum of R. solani. Disease incidence of sheath blight was observed once a week started at 2 week after planting. Data indicated that in both season, form of inoculum significantly affect the development of rice sheath blight. Highest disease incidence was observed in plots receiving fresh infected rice straw as the primary inoculum, indicating that this form of inoculum was the most efficient for rice sheath blight development. The other form appeared to be effective as primary source of inoculum, were decomposed infected rice straw and fresh infected weeds. In tropical rice ecosystem such as in Indonesia, sclerotia appeared to be not as an important primary inoculum for rice sheath blight. Such information would be of important as the basic of sheath blight management in Indonesia, since incorporation of fresh rice straw into the paddy field prior to planting is a common practice in Indonesian rice ecosystem.